PERANCANGAN APLIKASI E-ARSIP MENGGUNAKAN ALGORITMA SEQUENTIAL SEARCH UNTUK PENGARSIPAN SURAT PADA PT. VISI KARYA PRAKARSA - Yudi Herdiana (COMPUTING | Jurnal Informatika, 2023)
This research addresses the issue of letter archiving at PT. Visi Karya Prakarsa by designing an E-Archiving application that implements the Sequential Search algorithm. The purpose of this study is to develop an application capable of facilitating the letter search system with the necessary flexibility. The study was conducted within the company's environment, and through interviews with staff, constraints in letter management were identified, including unclear archiving procedures, irregular letter numbering, and deficiencies in management and monitoring. The limitations of the letter management division lead to delays in the letter approval process and reliance on personal communication channels for delivery. This research aims to design a computerized system that can generate incoming and outgoing letter reports, addressing archiving issues. A qualitative approach using the SDLC waterfall model is employed in the application design. PHP programming language, Bootstrap framework, and MySQL as the database are used in the implementation process. The results of this research are expected to provide benefits in the form of a digital Archive application with the implementation of the Sequential Search algorithm. This application is anticipated to rectify irregular letter archiving issues within the company, provide solutions for the approval and delivery process of letters, and offer guidance for enhancing corporate archive management.